Primary congenital hypothyroidism: a clinical review - Cavarzere, Paolo; Mancioppi, Valentina; Battiston, Riccardo; Lupieri, Valentina; Morandi, Anita; Maffeis, Claudio (Frontiers in Endocrinology, 2025)
Congenital hypothyroidism (CH) is the most common neonatal endocrine disorder. It is one of the clinical conditions that has benefited most from the introduction of newborn screening 50 years ago, as clinical management has changed and long-term consequences have been significantly reduced. In areas where neonatal screening is active, most affected patients show a clinically normal phenotype and/or only mild symptoms. At the same time, thanks to a progressive reduction in the TSH level used as cut-off for neonatal screening, the number of cases of CH with gland in situ is increasing, while the number of patients with abnormal thyroid development has remained essentially unchanged over time. Furthermore, important changes are observed in managing patients with CH and gland in situ. On the one hand, they are subjected to genetic investigations to understand the underlying molecular mechanism; on the other hand, a reassessment of thyroid function is suggested starting from the sixth month of life if their L-thyroxine requirement is low. This review aims to describe the clinical approach to CH and to optimize the management and treatment of this disease.